Cultural misunderstandings : the french-american experience - Carroll, Raymonde; Volk, Carol ([S.l.] : University Of Chicago Press, 1990)
Raymonde Carroll presents an intriguing and thoughtful analysis of the many ways French and Americans$1 (Band indeed any members of different cultures$1 (Bcan misinterpret each other, even when ostensibly speaking the same language. Cultural misunderstandings, Carroll points out, can arise even where we least expect them$1 (Bin our closest relationships. The revealing vignettes that Carroll relates, and her perceptive comments, bring to light some fundamental differences in French and American presuppositions about love, friendship, and raising children, as well as such everyday activities as using the telephone or asking for information.s
Keywords: Americans--Communication; France; French--Communication; Intercultural communication; Peacemakers (MacMillan, Margaret); United States